BIBLIOMETRIC ANALYSIS OF ONLINE DIGITAL BUSINESS FOR INDIGENOUS AND ETHNIC COMMUNITY USING VOSVIEWER - Zulazeze Sahri; Zulkifli Halim (Journal of Islamic, Social, Economics and Development, 2023)
This study aims to conduct a bibliometric analysis using the Scopus database to examine the research trends in online digital business within the global indigenous ethnic community from 2012 to 2022. Based on the criteria acquired, 192 articles were identified from 267 papers. The articles have undergone analysis from an international journal that Scopus index. This study uses a combination of mapping analysis and the VOSViewer application. In addition to utilizing VOSViewer, this study employed the Scopus Online Database to retrieve and evaluate scholarly citations. The keyword is "Online Digital Business for Indigenous and Ethnic Community." The findings indicate a consistent annual growth in online business research on Indigenous and Ethnic communities. The United States is the leading contributor to global analysis, followed by Australia in second place. The analysis of the trajectory of Online Business for Indigenous communities research from 2012 to 2022 reveals the existence of six distinct clusters. The findings of this study have the potential to offer valuable help to researchers investigating online and digital commercial initiatives targeted toward indigenous and ethnic communities worldwide. Additionally, these results can serve as a guiding framework for future research endeavors in this area. This review is a valuable reference point for future research on Online Digital Business among Indigenous communities.